Oenococcus oeni in Chilean Red Wines: Technological and Genomic Characterization - Romero, Jaime; Ilabaca, Carolina; Ruiz, Mauricio; Jara, Carla (Frontiers in Microbiology, 2018)
The presence and load of species of LAB at the end of the malolactic fermentation (MLF) were investigated in 16 wineries from the different Chilean valleys (Limarí, Casablanca, Maipo, Rapel and Maule Valleys) during 2012 and 2013, using PCR-RFLP and qPCR. Oenococcus oeni was observed in 80% of the samples collected. Dominance of O. oeni was reflected in the bacterial load (O. oeni/total bacteria) measured by qPCR, corresponding to > 85% in most of the samples. A total of 178 LAB isolates were identified after sequencing molecular markers, 95 of them corresponded to O. oeni. Further genetic analyses were performed using MLST (7 genes) including 10 commercial strains; the results indicated that commercial strains were grouped together, while autochthonous strains distributed among different genetic clusters. To pre-select some autochthonous O. oeni, these isolates were also characterized based on technological tests such as ethanol tolerance (12, and 15%), SO2 resistance (0 and 80 mg l-1), and pH (3.1 and 3.6) and malic acid transformation (1,5 and 4 g l-1). For comparison purposes, commercial strain VP41 was also tested. Based on their technological performance, only 3 isolates were selected for further examination (genome analysis) and they were able to reduce malic acid concentration, to grow at low pH 3.1, 15% ethanol and 80 mg l-1 SO2. The genome analyses of three selected isolates were examined and compared to PSU-1 and VP41 strains to study their potential contribution to the organoleptic properties of the final product. The presence and homology of genes potentially related to aromatic profile were compared among those strains. The results indicated high conservation of malolactic enzyme (>99%) and the absence of some genes related to odor such as phenolic acid decarboxylase, in autochthonous strains. Genomic analysis also revealed that these strains shared 470 genes with VP41 and PSU-1 and that autochthonous strains harbor an interesting number of unique genes (>21). Altogether these results reveal the presence of local strains distinguishable from commercial strains at the genetic/genomic level and also having genomic traits that enforce their potential use as starter cultures.